Physiological and life history responses in a mayfly (Callibaetis floridanus) inhabiting ponds with saltwater intrusion - Cochran, Jamie K.; Funk, David H.; Buchwalter, David B. (Frontiers in Ecology and Evolution, 2023)
Freshwater salinity varies in natural systems and plays a role in species distribution. Anthropogenic alterations to freshwater salinity regimes include sea level rise and subsequent intrusion of saline waters to inland habitats. While mayflies are generalized to be sensitive to increasing salinity, we still know remarkably little about the physiological processes (and their plasticity) that determine the performance of species in a changing world. Here, we explored life-history outcomes and physiological plasticity in a population of Callibaetis floridanus (Ephemeroptera: Baetidae) from a coastal pond that routinely experiences saltwater intrusion. We reared naiads from egg hatch to adulthood across a gradient of increasing salinities (113, 5,020, 9,921 µS/cm). Radiotracer flux studies (22Na, 35SO4, and 45Ca) were conducted in naiads reared at each salinity, revealing a positive association between ionic concentration and uptake rates. However, the influence of rearing history on ionic influx rates was apparent when naiads were transferred from their respective rearing water to the other experimental conditions. For example, we observed that naiads reared in the low salinity treatment (113 µS/cm) had 10.8-fold higher Na uptake rates than naiads reared at 9,921µS/cm and transferred to 113 µS/cm. Additionally, naiads acclimated to the higher salinity water exhibited reduced uptake in ion-rich water relative to those reared in more dilute conditions (e.g., in 9,921 µS/cm water, 113 and 5,020µS/cm acclimated naiads had 1.5- and 1.1-fold higher Na uptake rates than 9,921µS/cm acclimated naiads, respectively). We found no significant changes in survival (80±4.4%, mean±s.e.m.) or naiad development time (24±0.3 days, mean±s.e.m.) across these treatments but did observe a 27% decrease in subimago female body weight in the most dilute condition. This reduction in female weight was associated with higher oxygen consumption rates in naiads relative to the other rearing conditions. Collectively, these data suggests that saline adapted C. floridanus may be more energetically challenged in dilute conditions, which differs from previous observations in other mayfly species.